Socioeconomic determinants of COVID-19 infections and mortality: Evidence from England and Wales - Filipa Sá (Institute of Labor Economics (IZA), 2020)
I use simple correlations and regression analysis to study how the number of confirmed Covid-19 cases and the number of deaths with Covid-19 per 100,000 people is related with the socioeconomic characteristics of local areas in England and Wales. I find that local areas that have larger households, worse levels of self-reported health and a larger fraction of people using public transport have more Covid-19 infections per 100,000 people. For mortality, household size and use of public transport are less important, but there is a clear relation with age, ethnicity and self-reported health. Local areas with an older population, a larger share of black or Asian population and worse levels of self-reported health have more Covid-19 deaths per 100,000 people. To prevent the spread of infection and reduce mortality, policymakers should introduce measures to improve housing conditions and improve the health of the population. Also, as many countries now begin to relax lockdown measures, they should pay particular attention to reducing the risk of infection in public transport.
Keywords: I1; 330; COVID-19